POLYPHENOLS: ITS INGESTION IN FRUITS AND VEGETABLES AS A PROTECTIVE ACTION FOR HUMAN HEALTH FROM STRESS AGAINST COVID-19 - Argota-Pérez, George (2020)
Polyphenols are compounds of secondary metabolism in plants and their action is recognized in the control against free radicals and reactive oxygen species. Th e study aimed to indicate polyphenols and their intake in fruits and vegetables as a protective action for human health due to stress against Covid-19. Given the rapid spread of the emerging pandemic Covid-19, it continues to be of great concern due to the mortality that occurs globally and there is no doubt about the level of stress in the population. Attempts to fl atten the epidemiological curve are diverse in that Covid-19 could not only aff ect psycho-mentally, but some non-communicable diseases may perhaps debut. Considering the serious situation, from the axiological point of view, a question arises: can the daily consumption of fruits and vegetables in the diet patterns generate, from the metabolic point of view, any potentiating impact on immunology against COVID-19?